2010
DOI: 10.1007/s11703-009-0089-8
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the research on the AsA-GSH cycle in horticultural crops

Abstract: The adaptation of plants to stressed environments depends greatly upon the metabolic level of antioxidant systems within their bodies. Among the enzymatic antioxidant systems, the AsA-GSH cycle occupies a vital place and has become a hot research field in recent years. The AsA-GSH cycle can directly scavenge H 2 O 2 produced in plants on one hand, and the antioxidants AsA and GSH produced in the cycle can also scavenge other species of active oxygen by means of additional pathways on the other hand. Environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 46 publications
(38 reference statements)
3
44
0
Order By: Relevance
“…Non-enzymatic antioxidants include carotenoids, ascorbate (AsA), glutathione (GSH), flavanones, and anthocyanins [12,13]. The AsA-GSH cycle, an important antioxidant system, can maintain an appropriate oxidative and reductive environment in plants under stress [14]. GPX is another important ROS-scavenging enzyme that uses GSH to reduce H 2 O 2 as well as organic and lipid hydroperoxides.…”
Section: Introductionmentioning
confidence: 99%
“…Non-enzymatic antioxidants include carotenoids, ascorbate (AsA), glutathione (GSH), flavanones, and anthocyanins [12,13]. The AsA-GSH cycle, an important antioxidant system, can maintain an appropriate oxidative and reductive environment in plants under stress [14]. GPX is another important ROS-scavenging enzyme that uses GSH to reduce H 2 O 2 as well as organic and lipid hydroperoxides.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the overexpression of a DHAR gene has been shown to increase AsA levels and enhance cold tolerance in tobacco (Le Martret et al, 2011). However, studies of this kind have been limited thus far in horticultural crops (Li et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…After the fruits encountered high-temperature stress at 45°C, APX, GR, and MDAR activity increased initially, but the time for peak activity occurrence varied with individual enzymes, with APX at 1 h, 33.9% higher than the control, and with MDAR and GR at 3 and 5 h, respectively, 10% and 19.4% higher than the control. The results suggested that there was a given sequence in the time response of APX, MDAR, and GR to high-temperature stress, which was related closely to their posts in the cycle (Li et al, 2010). In this experiment, although APX, MDAR, and GR activity showed a certain degree of increase at 25°C, the level of membrane lipid superoxidation in high-temperature treated fruits was significantly higher than that of the control after 3 h, showing that during initial stage of high-temperature treatment, the activity increase for each of the antioxidant enzymes was merely a kind of heat-shock and selfdefensive response.…”
Section: Discussionmentioning
confidence: 80%
“…Due to electrolyte leakage and cell contents oxidization, fruit peel frequently shows typical symptoms like brown or dark color. It has been proved that the AsA-GSH cycle is an important antioxidant system in plants, in which APX, MDAR, and GR are key enzymes that represent the initial, middle, and final posts in the whole cycle (Li et al, 2010). Therefore, the study on changing patterns of relevant enzymes in the AsA-GSH cycle under high temperature and excessive sunlight conditions is helpful to understand how these enzymes response to environmental stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation